Simulated economic and nutritional impacts of irrigated fodder and crossbred cows on farm households in southern Ethiopia - Bizimana, Jean-Claude; Bezabih, Melkamu; Adie, Aberra; Kiker, Gregory A. (Elsevier, 2023)
The livestock sector is one of the main pillars of Ethiopia’s economy. Despite its importance, several constraints related to livestock production such as low productivity, remain a major barrier to the development of the livestock sector in Ethiopia. Improving animal feed resources and breeds can have impacts on both household income and nutrition. Small scale irrigation (SSI) technologies are used to grow and improve yields of fodder with the purpose to feed animals, generate income and improve human nutrition through the consumption of animal products. A farm level economic and nutrition simulation model (FARMSIM) is used to evaluate the potential nutritional and economic impacts of the SSI technologies on households in southern Ethiopia, Lemo district. In the baseline scenario, fodder is grown on limited land with minimal input while in alternative scenarios, more land and input are allocated to fodder during the dry season due to irrigation. Results show that the annual average profit under alternative scenarios is almost twice that of the baseline. However, the distribution results highlight the risk associated with high production costs from SSI technologies investments. The nutrition results show that the quantities of products consumed by families in alternative scenarios meet the minimum daily requirements for calories, proteins, iron, and vitamin A but were insufficient for calcium and fat. A large deficit in vitamin A is observed under the baseline scenario, in addition to calcium and fat. However, forgoing some income to increase the quantity of animal products consumed at home led to nutrition improvement in Lemo district.